Meminimalisir Tingkat Kecacatan Produk Biji Kopi Robusta Arjuno Pada Proses Produksi Untuk Meningkatkan Kualitas Produk - Wibowo, Andreas Edo; Khoiroh, Siti Muhimatul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Kopikula Roastery Coffee, a producer of Robusta Arjuno coffee beans, experienced aproduction decline due to product defects. By using Statistical Process Control (SPC), the quality was analyzed, and the causes of defects were identified. The company had a low quality control level, with a defect percentage of 2.97%. Factors such as workers, methods, environment, and machinery contributed to the defects. To minimize the number of defects, standardization, improved production methods, workspace enhancements, and machinery component replacements were implemented. As a result, the defect percentage decreased to 1.84%. Kopikula Roastery Coffee is dedicated to continuously improving product quality through effective quality control measures, aiming for customer satisfaction and upholding its reputation as a producer of high-quality coffee beans.